CULTURAL COMMUNICATION STRATEGY IN DISTINGUISHING LIFE STYLE AND LIFESTYLE IN INDIGENOUS COMMUNITIES - Subekti, Priyo; Sjuchro, Dian Wardiana; Tri, Nguyen Minh (ASPIRATION Journal, 2025)
This paper investigates how the indigenous community of Kampung Naga, West Java, Indonesia uses cultural communication techniques to preserve a traditional way of life under growing modern challenges. The study reveals five main themes by means of a qualitative phenomenological approach and thematic analysis: value inheritance through role modelling, symbolic communication in cultural practices, selective adaptation to modern culture, ecological and spiritual relationships with nature, and the role of social rituals in maintaining cultural identity. In-depth interviews, participatory observation, and documentation involving nine informants-elders, birth attendants, women, youth, and returnees from metropolitan areas-data were gathered. The results indicate that instead of passive preservation, the Kampung Naga community maintains its way of life by means of a dynamic process of cultural negotiation. Daily activities and intergenerational role models help people to assimilate cultural beliefs rather than formal education. Symbols like holy woods, birth ceremonies, and bans on power use are communicative devices mediating identity, spirituality, and resistance. These techniques mirror socio-cultural, semiotic, and phenomenological communication traditions in which meaning is manifested in action and group memory